Satisfacción e insatisfacción laboral: una oportunidad para pensar la profesión odontológica (2014)
ABSTRACT: This article analyzes both labor satisfaction and dissatisfaction in dentists working in Antioquia (Colombia), within the scope of health regulation reforms after “Ley 100 de 1993” (Act 100 of 1993). Methods: Satisfaction and dissatisfaction as subjective aspects of the work have conducted to the use of a qualitative framework through semi-structured interviews held on 13 female and 5 male dentists, after confirmation of their consent agreement. Results: satisfaction and dissatisfaction in dentists coexist within their daily practice, and are associated to professional autonomy and transformation dynamics in healthcare delivery and patient care. The previous related to a regulatory, labor and social context in which dentists perform their professional practice. Conclusion: both satisfaction and dissatisfaction mentioned by dentists constitute opportunities for the strengthening and improving of the profession, in the quest for harmonization among possibilities of access, quality and opportunities in healthcare care delivery on patients, along with professional autonomy conditions for dentists.